ความสัมพันธ์ระหว่างการทำงานกะกับความเสี่ยงต่อการเป็นโรคเบาหวานชนิดที่ 2 และภาวะก่อนเป็นเบาหวานในบุคลากร 2 องค์กรขนาดใหญ่ในกรุงเทพมหานคร - นิต หาญประเทศ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This retrospective cohort study aimed to examine the association between shift work and the incidence of type 2 diabetes and pre-diabetes among the workers in two large organizations in Bangkok. This study was conducted among 5,947 workers (4,647 females and 1,300 males) aged ≤ 60 years old of the Thai Red Cross Society and Chulalongkorn University, Bangkok. Samples required a normal fasting plasma glucose (FPG) level (<100 mg/dL) at baseline and had at least two health check-up results during 2009-2016. The shift work exposure was assessed by using a self-administered questionnaire and the incidence of type 2 diabetes and pre-diabetes was assessed by using FPG levels which were measured annually. The association between shift work and type 2 diabetes and pre-diabetes was analyzed by Cox’s proportional hazard models to estimate multivariate hazard ratios (HR) with 95% confidence interval (95% CI). The results found that the proportion of shift workers was 23.7%. 97 and 47 new type 2 diabetes cases had developed among the non- and shift workers respectively, with the corresponding incidence rates of 4.48 and 6.18 per 1,000 person-years. And 994 and 335 new pre-diabetes cases had developed among the non-and shift workers respectively, with the corresponding incidence rates of 53.43 and 50.74 per 1,000 person-years. After adjusting for potential confounding factors, male shift workers had a significantly increased risk of type 2 diabetes and pre-diabetes [(HR 2.98, 95% CI: 1.58, 5.62) and (HR 1.86, 95% CI: 1.43, 2.41) respectively], as compared to the non-shift workers while this was less obvious among women. This study demonstrated that shift work is associated with increased risk of type 2 diabetes and pre-diabetes, especially in the male. Mechanism of the association between shift work and type 2 diabetes risk need further investigations.